2008
DOI: 10.1002/cyto.a.20642
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to improve the direct ex vivo detection of low frequency antigen‐specific CD8+ T cells with peptide‐major histocompatibility complex class I tetramers

Abstract: The ability to quantify and characterize antigen-specific CD8 1 T cells irrespective of functional readouts using fluorochrome-conjugated peptide-major histocompatibility complex class I (pMHCI) tetramers in conjunction with flow cytometry has transformed our understanding of cellular immune responses over the past decade. In the case of prevalent CD8 1 T cell populations that engage cognate pMHCI tetramers with high avidities, direct ex vivo identification and subsequent data interpretation is relatively stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…Consistent with this notion, greater proportions of CD8 T cells with a stem cell memory phenotype (T SCM ; CD27 + CD45RO 2 CD95 + CCR7 + ) (28) were present in type 1 diabetic patients compared with healthy control subjects across all pooled b-cell specificities (P = 0.025), as well as individually within the autoreactive populations specific for PPI [15][16][17][18][19][20][21][22][23][24] (P = 0.05) and InsB [10][11][12][13][14][15][16][17][18] (P = 0.029). Moreover, single-marker analyses revealed that b-cell-specific CD8 T cells expressed higher frequencies of CD57 (P = 0.0002) and CD95 (P , 0.0001) in type 1 diabetic patients compared with healthy control subjects (Fig.…”
Section: Ex Vivo Identification Of B-cell-specific Cd8 T Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with this notion, greater proportions of CD8 T cells with a stem cell memory phenotype (T SCM ; CD27 + CD45RO 2 CD95 + CCR7 + ) (28) were present in type 1 diabetic patients compared with healthy control subjects across all pooled b-cell specificities (P = 0.025), as well as individually within the autoreactive populations specific for PPI [15][16][17][18][19][20][21][22][23][24] (P = 0.05) and InsB [10][11][12][13][14][15][16][17][18] (P = 0.029). Moreover, single-marker analyses revealed that b-cell-specific CD8 T cells expressed higher frequencies of CD57 (P = 0.0002) and CD95 (P , 0.0001) in type 1 diabetic patients compared with healthy control subjects (Fig.…”
Section: Ex Vivo Identification Of B-cell-specific Cd8 T Cellsmentioning
confidence: 83%
“…In particular, antigen-specific CD8 T cells can now be enumerated routinely by flow cytometry irrespective of functional outputs due to the advent of recombinant peptide-HLAI (pHLAI) proteins in various fluorochrome-tagged multimeric formats (10)(11)(12)(13). Moreover, developments in instrumentation and fluorochrome technology continue to expand the horizons of polychromatic flow cytometry (14,15), facilitating the identification of functionally distinct T cell subsets across a spectrum of phenotypic heterogeneity (16).…”
mentioning
confidence: 99%
“…This dual fluorochrome strategy, previously described for antigen-specific CD8 + effector T cells, allows the discrimination of signal and noise staining, as specific CD8 + Tregs will bind equally to each version of RT1.A a /Du51 tetramer, whereas random elements will not (26). Among double-positive stained events, nonpeptide-specific cells can be visualized and excluded, since they bind to a control tetramer bearing the same heavy-chain RT1.A a , but with an irrelevant associated peptide (Supplemental Figure 4C).…”
Section: Figurementioning
confidence: 99%
“…10,19,20 Flow cytometry for tetramer analysis Sample staining was performed in 50 L of phosphate-buffered saline (PBS)/1% fetal calf serum using 3 ϫ 10 6 PBMCs prestained with a violet amine-reactive dye (Aqua-blue or ViViD; Invitrogen) to eliminate dead cells from the final analysis. Fluorochrome-labeled HLA-A*0201 tetramers (1-2 g per test with respect to the peptide-major histocompatibility complex class I component) were added for 15 to 30 minutes at 37°C.…”
Section: Peptide-major Histocompatibility Complex Class I Tetrameric mentioning
confidence: 99%